2022
DOI: 10.21037/tlcr-22-761
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the artificial intelligence (AI)-based diagnostic model for bronchial lumen identification

Abstract: Background: Bronchoscopy is a key step in the diagnosis and treatment of respiratory diseases. However, the level of expertise varies among different bronchoscopists. Artificial intelligence (AI) may help them identify bronchial lumens. Thus, a bronchoscopy quality-control system based on AI was built to improve the performance of bronchoscopists.Methods: This single-center observational study consecutively collected bronchoscopy videos from Shanghai Chest Hospital and segmented each video into 31 different an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In this golden age of rapid advances in artificial intelligence (AI), the combination of AI and medicine poses a profound effect on every aspect of healthcare ( 23 ) with significant progress in image classification, segmentation, and object detection ( 24 , 25 ), which shed light on the difficult FB management by bronchoscopy. For instance, Li et al built a bronchoscopy quality-control system based on AI and showed that the supplemental application of the AI system could reduce the differences in the endoscopic skills of doctors with different levels of experience ( 26 ). However, at present, only limited studies have been taken in the application of AI to bronchoscopy ( Supplementary Table S1 ) ( 26 31 ), most of which are mainly focused on recognizing tumors ( 27 , 28 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this golden age of rapid advances in artificial intelligence (AI), the combination of AI and medicine poses a profound effect on every aspect of healthcare ( 23 ) with significant progress in image classification, segmentation, and object detection ( 24 , 25 ), which shed light on the difficult FB management by bronchoscopy. For instance, Li et al built a bronchoscopy quality-control system based on AI and showed that the supplemental application of the AI system could reduce the differences in the endoscopic skills of doctors with different levels of experience ( 26 ). However, at present, only limited studies have been taken in the application of AI to bronchoscopy ( Supplementary Table S1 ) ( 26 31 ), most of which are mainly focused on recognizing tumors ( 27 , 28 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Li et al built a bronchoscopy quality-control system based on AI and showed that the supplemental application of the AI system could reduce the differences in the endoscopic skills of doctors with different levels of experience ( 26 ). However, at present, only limited studies have been taken in the application of AI to bronchoscopy ( Supplementary Table S1 ) ( 26 31 ), most of which are mainly focused on recognizing tumors ( 27 , 28 , 31 ). Particularly, there is a research gap in the application of AI in complicated FB aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Li et al 31 also recognizes the anatomical positions under bronchoscopy. However, there were several differences between our studies.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy for the determination of anatomical location was 38–51% in anesthesiologists and 68–82% in pulmonologists, whereas the pretrained CNN model showed an 86% accuracy. Li et al [24 ▪ ] reported bronchial tree anatomical identification using trained CNN models. They included images of not only the carina and both main bronchi, but also all segmental bronchi that are usually observed during bronchoscopy.…”
Section: Artificial Intelligence In Endoscopymentioning
confidence: 99%